Akaluc bioluminescence offers superior sensitivity to track in vivo glioma expansion. Issue 1 (10th October 2020) - Bozec, Dominique; Sattiraju, Anirudh; Bouras, Alexandros; Jesu Raj, Joe G; Rivera, Daniel; Huang, Yong; Junqueira Alves, Chrystian; Tejero, Rut; Tsankova, Nadejda M; Zou, Hongyan; Hadjipanayis, Constantinos; Friedel, Roland H
Abstract: Background: Longitudinal tracking of tumor growth using noninvasive bioluminescence imaging (BLI) is a key approach for studies of in vivo cancer models, with particular relevance for investigations of malignant gliomas in rodent intracranial transplant paradigms. Akaluciferase (Akaluc) is a new BLI system with higher signal strength than standard firefly luciferase (Fluc). Here, we establish Akaluc BLI as a sensitive method for in vivo tracking of glioma expansion. Methods: We engineered a lentiviral vector for expression of Akaluc in high-grade glioma cell lines, including patient-derived glioma stem cell (GSC) lines. Akaluc-expressing glioma cells were compared to matching cells expressing Fluc in both in vitro and in vivo BLI assays. We also conducted proof-of-principle BLI studies with intracranial transplant cohorts receiving chemoradiation therapy. Results: Akaluc-expressing glioma cells produced more than 10 times higher BLI signals than Fluc-expressing counterparts when examined in vitro, and more than 100-fold higher signals when compared to Fluc-expressing counterparts in intracranial transplant models in vivo. The high sensitivity of Akaluc permitted detection of intracranial glioma transplants starting as early as 4 h after implantation and with as little as 5000 transplanted cells. The sensitivity of the system allowed us to follow engraftment and expansion of intracranial transplants of GSC lines. Akaluc was also robust for sensitive detection of in vivo tumor regression after therapy and subsequent relapse. Conclusion: Akaluc BLI offers superior sensitivity for in vivo tracking of glioma in the intracranial transplant paradigm, facilitating sensitive approaches for the study of glioma growth and response to therapy.